Membaca Permulaan Melalui Aplikasi Zoom Meeting pada Masa Pembelajaran Daring Kelas IIC SD Negeri 005 Tarakan - Safitri, Nila (Indo-MathEdu Intellectuals Journal, 2023)
This study aims to present the results of the effectiveness of the zoom meeting application in improving initial reading during online learning. The results of the learning activities that have been carried out can be concluded that zoom meetings are effectively used in initial reading learning because there is an increase, namely from 22 students, 10 people can read fluently, 9 students need guidance, and 3 students cannot read. Zoom meeting has many features that support the learning process such as Record, Chat, Share Screen, Mute &; Unmute. Therefore, teachers must understand and use effective technology in supporting the online learning process, especially beginning reading in grade II